A Rare Case of Severe Hemophilia B Combined with Hematomesenchymal Dysplasia - Muratova, Fatima; Mussabekova, Zhanna; Kazymov, Maxut; Sturov, Viktor (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The prevalence of hemophilia B in the global population is approximately 1:60,000. Undifferentiated systemic mesenchymal dysplasia (uSMD) is diagnosed rather frequently, about 1:5, according to Russian authors; no data on uSMD prevalence in other countries are available. The combination of hemophilia and uSMD has grouped under the term hematomesenchymal dysplasia (HMD). This combination significantly worsens the clinical picture, prognosis, and quality of life of the patient. AIM: In this article, we present a rare clinical case of a child with a combination of hemophilia B and HMD. CASE REPORT: A clinical case of a male patient, 5 years old with hemophilia B, severe form combined with HMD, complicated by hemothorax, abscessed pulmonary lobe hematoma has presented. The presence of HMD and the above complications had an unfavorable effect on the severity of the clinical picture and the abnormal response to treatment. The main diagnostic procedures were the assessment of the phenotypic signs of HMD in combination with laboratory and instrumental examination methods such as ultrasound, computed tomography (CT) scan, and echocardiography. Vital treatment is factor IX replacement therapy and supportive one. CONCLUSION: This clinical example highlights the importance of clinical alertness to hereditary coagulopathies, which often lead to life threatening, sometimes disabling complications that significantly reduce the quality of life of children with hemophilia. Consequently, full-scale epidemiological studies of the prevalence of HMD in the population are an urgent task for the near future.